Analisis Putusan Hakim Terhadap Pelaku Tindak Pidana Perdagangan Satwa Liar yang di Lindungi Jenis Siamang (Studi Putusan Nomor 134/Pid.B/LH/2023/Pn. Kla) - Theo Gorand Gabrielo Sihite; Maya Shafira; Fristia Berdian Tamza (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Illegal trafficking of protected wildlife is an activity that is a threat to the survival of wildlife, Illegal trafficking categorized as a crime against wildlife includes: intentionally capturing, storing, possessing, maintaining, transporting and trading protected animals in a living condition. The problem in this thesis is what is the basis for the judge's legal considerations in passing a verdict against the perpetrator of the crime of trafficking in protected wildlife of the Siamang species in Decision Number: 134 / Pid.B / LH / 2023 / Pn Kla? is the judge's decision in imposing the sentence in accordance with substantive justice?, The research method used is normative and empirical juridical, The data used is primary and secondary data, data collection with literature studies and interviews. While data processing through the stages of data examination, data selection, data classification, and data systematization. The data that has been presented in the form of a description, discussed and analyzed descriptively qualitatively, to then draw conclusions. Based on the results of the study, it is known that the consideration of the Judge in Decision Number: 134 / Pid.B / LH / 2023 / Pn Kla in deciding the criminal case of trade in protected wildlife species of siamang, the Judge in Decision Number: 134 / Pid.B / LH / 2023 / Pn Kla related to the criminal act of trade in siamang species of wildlife considered the legal, sociological, and philosophical aspects according to Ahmad Rifai's theory. The legal aspect includes the sufficiency of evidence and the fulfillment of the elements of Article 40 Paragraph 2 in conjunction with Article 21 Paragraph 2 of Law No. 5 of 1990 concerning the Conservation of Natural Resources and Ecosystems. Sociologically, the judge sees the impact of the defendant's actions on society and the environment. From a philosophical perspective, punishment is seen not as revenge, but an effort to educate the defendant not to repeat his actions. Finally, the judge sentenced him to 1 year and 4 months in prison and a fine of Rp25,000,000, subsidiary to 1 month in prison if the fine is not paid. The suggestion is that the government, law enforcement and stakeholders are expected to increase education to the community, especially around national parks/protected forests, not to trade in protected animals. This is important to prevent similar crimes and maintain the existence of protected animals in their habitat.